Follow the heart or the mind? Examining cognitive and affective attitude on HPV vaccination intention. Issue 2 (15th March 2021) - Xiao, Xizhu
ABSTRACT: Human papillomavirus (HPV) is associated with various serious diseases including cervical cancer and genital warts. Although the HPV vaccine has been commended as a breakthrough for preventing HPV and HPV-related diseases, the uptake rate remains inadequate and lagging. This dissatisfaction is possibly attributed to a component of interventions that is insufficiently related to individuals' intentions to get vaccinated against HPV – attitude. With a sample of 430 participants, this study examined which attitudinal component (cognitive vs. affective) is a stronger influencer on the intention to get the HPV vaccine. This study also investigated the influence of risk perceptions of HPV on the attitude and intention of getting the vaccine. Results revealed that cognitive attitude is the sole predictor of intention and mediates the relationship between perceived susceptibility to HPV and the intention to get the vaccine. Theoretical and practical contributions to the field of health communication and HPV vaccine promotion are further discussed.